Resistencia de genotipos de plátano (Musa sp.) a Sigatoka Negra (Mycosphaerella fijiensis) en San Martín - Dávila Amasifuen, Mario (2010)
With the purpose of determining the agronomic characteristics and his genetics resistant genética a the black sikatoka of the plant and fruit FHIA comparators with silk clone, under Agro climatic conditions of the San Martin Region, investigation Word It was developed from January 2001 to September 2002 in the district of Cacatachi province and Region of San Martín, South Latitude 6o 22, West Longitude 76o 12, Altitude 330 meters over the sea level inside the dry tropical forest. We used DBCR with 5 treatments and four repetitions. We evaluated agronomic characteristics, genetics and health. The FHIA 2 was the most resistant to the black sigatoka illness caused by the Mycosphaerella fijiensis fungus, in the San Martín Region, because it reached up with the lower averages over the average pondered of Infection (0,7 and 0,14 ), upper percentages of healthy leaves (95,00 y 86,40%) to the flowering and harvest, more number of functional leaves to the bunch's Birth and harvest ( 12 and 13,37 ), performance (27.03Kg with 154 fingers per bunch), with finger thickness of 15 centimeters. All the FHIA were precocious and the bunch apparition happened approximately 3 months before the harvest. The FHIA 3 and 23 got the biggest finger thickness of 79.25 centimeters, while the FHIA 2 and 18 reported the greatest fruits weights (205 g), the FHIA 3 with 1,55 it reported the most high infection grade HMJA and its performance was of 36,03 tons per acre, THE FHIA 23 got the most high quantity of hands per bunch with 10 hands, and fingers of 17 centimeters long. In the economic analysis (bunches per acre) the FHIA 3 reported a whole benefit of S/. 1,194.39 new soles and in the economic analysis (performance in tons per acre) it reported a whole benefit of S/. 706.38 nuevos soles superior to the rest of the clones.